Theory of Reasoned Action as a Framework for Analyzing Investment Knowledge in Generation Z - Satria Lintang Satria Lintang; Nurul Mufida; Hasnadia Rusdy; Arjuna Agung Grison Masiku (Fundamental and Applied Management Journal, 2024)
This study aims to explore investment knowledge among students at Universitas Negeri Makassar using the Theory of Reasoned Action as a framework. The research examines how investment knowledge is influenced by various factors such as behavioral intentions, financial literacy, cognitive biases, social behavior, attitudes toward behavior, and subjective norms. By applying the Theory of Reasoned Action, this study seeks to explain how these factors shape students' decision-making processes in investment. A descriptive analysis method was employed, with data collected through surveys and analyzed using SPSS software. The study involved a population of students from Universitas Negeri Makassar, focusing on how their attitudes, intentions, and social influences impact their investment decisions. The findings indicate that students’ investment decisions are significantly shaped by their attitudes toward investment behavior and their intentions to act. The results highlight the importance of developing financial literacy and addressing cognitive biases to improve students' investment knowledge. This research has implications for educational programs, emphasizing the need to enhance students' potential and equip them with the necessary skills and knowledge to make informed investment decisions.